Single Center Study: Using Pre-Treatment Neutrophil to Lymphocyte Ratio as a Predictor of Outcome in Metastatic Breast Cancer Patients Treated with Cyclin Dependent Kinase 4/6 Inhibitors - Saleem, Warda; Batool Zaidi, Syeda Samnita; Rizwan, Sidrah; Salim Naviwala, Muhammad Saad; Ahmed, Faiza; Zehra, Nawazish; Zaki, Adeeba; Rashid, Yasmin A. (Indus Journal of Bioscience Research, 2025)
Introduction: Breast cancer is the most prevalent cancer among women worldwide, and prognostic markers are vital for predicting outcomes. Systemic inflammatory markers, such as neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and lymphopenia, have been associated with tumor progression and prognosis. This study aimed to assess the predictive effects of NLR, LMR, and lymphopenia in Pakistani women receiving CDK4/6 inhibitors alongside endocrine therapy for metastatic breast cancer. Materials and Methods: We conducted a retrospective study at Aga Khan University Hospital, Karachi, from January 2018 to September 2024. Blood tests conducted within one week before treatment initiation were analyzed for NLR, LMR, and lymphopenia. Results: Among 53 evaluable patients, those with pre-treatment NLR